2015
DOI: 10.1111/cmi.12431
|View full text |Cite
|
Sign up to set email alerts
|

The C ‐terminal tail of tetraspanin proteins regulates their intracellular distribution in the parasite T richomonas vaginalis

Abstract: SummaryThe parasite Trichomonas vaginalis is the causative agent of trichomoniasis, a prevalent sexually transmitted infection. Here, we report the cellular analysis of T. vaginalis tetraspanin family (TvTSPs). This family of membrane proteins has been implicated in cell adhesion, migration and proliferation in vertebrates. We found that the expression of several members of the family is up-regulated upon contact with vaginal ectocervical cells. We demonstrate that most TvTSPs are localized on the surface and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…We have previously noted that highly adherent strains generally aggregate in cell culture, in contrast to less‐adherent strains (such as G3; Coceres et al, ). Moreover, this observation has been correlated with the ability of the strain to adhere and be cytotoxic to host cells (Coceres et al, ; Lustig et al, ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously noted that highly adherent strains generally aggregate in cell culture, in contrast to less‐adherent strains (such as G3; Coceres et al, ). Moreover, this observation has been correlated with the ability of the strain to adhere and be cytotoxic to host cells (Coceres et al, ; Lustig et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…Despite being of critical importance to the survival of T. vaginalis , the mechanisms used to establish an infection and thrive within its host are poorly defined. Different T. vaginalis strains are highly variable in their adherence, aggregation, and cytolysis capacity (Coceres et al, ; Lustig, Ryan, Secor, & Johnson, ; Rojas et al, ), even when they have almost identical amino acid sequences (Leitsch et al, ; de Miguel et al, ; and our unpublished data). These differences in the pathogenic phenotype could suggest that the proteins mediating these interactions vary greatly, either in abundance or in type between strains (Lustig et al, ).…”
Section: Introductionmentioning
confidence: 80%
“…In general, tetraspanins are known to be involved in cell proliferation, adhesion, signalling and migration [56]. Recently, it was shown that the tetraspanin TvTSP8 of Trichomonas vaginalis is involved in parasite-parasite communication [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies identified tetraspanins, proteins that are markers of exosomes 101. T. vaginalis exosomes are about 50-100 nm in diameter and contain RNA and a variety of proteins.…”
Section: Pathogenicity - Opening the "Black Box" Of Trichomonas Vaginmentioning
confidence: 99%